THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT IN LINKING TRANSFORMATIONAL LEADERSHIP AND EMPLOYEE WELL-BEING TO EMPLOYEE PERFORMANCE (Evidence from a State-Owned Enterprise Subsidiary) - Hartoko Suryomedianto; Zainul Kisman (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
This study examines the mediating role of employee engagement in the relationship between transformational leadership, employee well-being, and employee performance within a state- owned enterprise (SOE) subsidiary operating in the Testing, Inspection, and Certification (TIC) sector. A quantitative explanatory design was employed using census sampling of 173 employees at the Head Office of an Indonesian SOE subsidiary. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), following measurement and structural model assessment procedures. Transformational leadership and employee well-being significantly and positively influence employee engagement. Employee engagement exerts the strongest direct effect on employee performance and partially mediates the relationships between transformational leadership, employee well-being, and performance. The results confirm engagement as a central psychological mechanism through which leadership and well-being initiatives translate into performance outcomes. This study contributes to engagement and leadership literature by integrating transformational leadership and employee well-being into a unified mediation model within an SOE context—an institutional setting characterized by bureaucratic governance yet performance-driven service operations. The findings extend engagement theory by positioning employee engagement as a strategic performance-enabling construct in hybrid public–corporate organizations.